A Convenient Protecting Group for Uridine Ureido Nitrogen: (4,4′-Bisfluorophenyl)methoxymethyl Group - Mitachi, Katsuhiko; Mingle, David; Kurosu, Michio (Synthesis, 2021)
(4,4′-Bisfluorophenyl)methoxymethyl (BFPM) group of uridine ureido nitrogen shows good relative stability in a variety of chemical transformation reactions for uridine. The BFPM group can be cleaved by 2% of TFA in CH2Cl2 without affecting the Boc group.
Keywords: uridine; ureido nitrogen; diarylmethoxymethyl group; [bis(4-fluorophenyl)methoxy]methyl group; chemical transformations; muraymycin synthesis